Low-dimensional emissive states in non-stoichiometric methylammonium lead halide perovskites. Issue 18 (12th April 2019) - Freestone, Benjamin G.; Smith, Joel A.; Piana, Giacomo; Kilbride, Rachel C.; Parnell, Andrew J.; Sortino, Luca; Coles, David M.; Ball, Orianna B.; Martsinovich, Natalia; Thompson, Courtney J.; Alanazi, Tarek I.; Game, Onkar S.; et al.
Abstract : Self-assembly of excitonic nanostructures from excess cationic MAI:PbCl2 perovskite solutions. Abstract : Mixed-halide perovskites prepared from methylammonium iodide and lead chloride (MAPbI3− x Cl x ) precursors are becoming increasingly well understood, however the effect of non-stoichiometry in this system is still not clear. Here, we create MAPbI3− x Cl x perovskites from starting mixtures containing an excess of MAI, and study them using a variety of structural and optical probes. Using grazing incidence X-ray scattering (GIWAXS) we demonstrate the existence of non-perovskite structures, and show that addition of hydroiodic acid (HI) also leads to similar low-dimensional phase formation. Photoluminescence spectroscopy performed at cryogenic temperatures indicates the existence of multiple emissive states between 510 nm and 605 nm resulting from a low dimensional phase (LDP) or multiple phases. By mapping the distribution of luminescence across the surface with submicron resolution, we found strong co-localisation of LDP emissive states. At certain blend ratios, emission is seen from both LDP states and methylammonium lead iodide perovskite (around 770 nm). Photoluminescence excitation spectroscopy of mixed-phase films reveals energy transfer, or a cascade, between different LDP states, but this process only occurs inefficiently to the surrounding perovskite. Time-resolved photoluminescence measurements demonstrate that LDP excited-state lifetimes decrease as a function of increasing temperature; a process consistent with a thermally-activated charge transfer process. Our work suggests that non-stoichiometric materials prepared via this processing route can lead to the formation of metastable LDPs with unique material properties that merit further investigation.